E-Module Development: Frog Jumping Game for Mentawai Inland Tribe Children Based on Local Wisdom - Komaini, Anton; Inarta, Gian Utomo; Kiram, Phil Yanuar; Handayani, Sri Gusti (LPPM Undiksha, 2023)
Motor development is very important in the stages of child development. Children's motor development is in accordance with the characteristics of children, namely playing so that good motor skills are needed to be able to support children's daily activities. This study aims to analyze the results of e-module development and gross motor skills of students in Mentawai district. This research is a type of development research (R&D). This research was developed using the ADDIE development model. The instruments used were media expert validation questionnaires, material expert validation questionnaires, response questionnaires, and student motor skills observation sheets. The population of this study were students at Mentawai district, selected by purposive sampling technique. In this study, the data analyzed by using descriptive statistics (mean, frequency, percentage, median mode) and inferential statistics (assumption tests and hypothesis testing in the form of tests and correlation tests). The results showed that the electronic modules produced were categorized as good and there were differences in the results of the gross motor skills of the students in Mentawai district before and after the use of e-modules. This can be seen from the significance values obtained, namely 0.000 and 0.030. The conclusion that can be drawn is the creation of an electronic module for the frog jump game with a good category based on the results of media expert validation and material expert validation that can be accessed via a smartphone or laptop.